RESULTS OF THE STUDY ON INDIVIDUAL AND PSYCHOLOGICAL CHARACTERISTICS OF A PERSONALITY AND THE STRESS RESISTANCE MANIFESTATION: GENDER ASPECT (Psychology Travelogs, 2023)
The article presents an analysis of the state of research on the problem of personality stress resistance, gender differences in individual psychological features of its manifestations. The relevance of the problem of increasing the stress resistance level of a modern person as a primary task of the state to maintain public peace, social stability, the ability to predict and manage the processes taking place in society is substantiated. The problem of stress resistance, which affects the physical and mental health of an individual, determines his well-being, and the problem of prevention of stress and increasing stress resistance level in modern society are particularly significant, due to social demand. A person who has a stable psyche, fully realizes his social roles, makes his professional and civic contribution to the common good, is an efficient employee, a good family man, constantly improves himself and harmonizes his interaction with the surrounding world.In the article, the concepts of “stress” and “stress resistance” were analyzed, and it was found that a significant part of researchers note their ambiguity, complexity, and insufficient development. At the same time, some issues of manifestations of stress resistance due to gender differences remain insufficiently studied, as well as the importance of the influence of individual psychological resources on stress resistance is underestimated.The results of the conducted experimental and research work were analyzed: the levels of men and women stress resistance were highlighted; it was determined that different levels of men and women stress resistance depend on the individual and psychological characteristics of the personality, among which the most significant are indicators of anxiety, temperament peculiarities and self-actualization of the personality; it was found that men with high stress resistance differ from women in higher emotional stability, higher values of tempo, self-respect, self-acceptance, lower indicators of reactive anxiety, emotionality and sensitivity to oneself. In turn, among examined individuals with a low level of stress resistance, men differ from women in higher emotional stability and lower indicators of reactive anxiety, emotionality, and social emotionality.
Keywords: individual and psychological characteristics of the personality; stress; stress resistance; sex